Should Scientists Communicate—and If So, with Whom? - Tschirgi, Robert D. (1973)
The contemporary criterion of professional success for an academic scientist is primarily his rate of publication in scholarly journals. This distorted and relatively uncritical valuation of the communication aspects of science has promoted an increasing deluge of increasingly redundant, dilute, and trivial publications. In a modern well-equipped research laboratory, producing publishable new observations can be a fairly simple process in many fields, especially if the relevance of the observations to either the advancement of the scientific world view or to a social need is inconsequential. This easy currency of rampant new observations has obscured the creative process of formulating new scientific concepts which are the ultimate refined product of the scientific enterprise. Perhaps scientists should talk less and think more.